Operations and Maintenance of Rural Infrastructure in Community-Driven Development and Community-Based Projects : Lessons Learned and Case Studies of Good Practice - Salomonsen, Andreas; Diachok, Myrtle (World Bank, Washington, DC, 2015)
This paper is organized into three main sections. Section one presents the background, objectives, scope, and limitations of the study. It also provides a general definition of OM and presents prototypical OM arrangements for rural CDD and community-based subprojects. Section two presents the detailed case studies for the seven selected projects. Section three summarizes the conclusions from the review and recommends steps for moving ahead. Five annexes provide extra background information, including the complete list of projects from which the seven main case studies were selected, as well as: examples of maintenance requirements for rural infrastructure; considerations for task teams planning for OM design and implementation; sample OM measures and timelines; and links to OM materials.